SHORT-TERM OUTCOMES OF TREATMENT OF CLOSED TIBIAL SHAFT FRACTURES MANAGED WITH LOCKED INTRAMEDULLARY NAILING AT 108 MILITARY CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the short-term outcomes of treatment outcomes of closed tibial shaft fractures managed with locked intramedullary nailing at 108 Military Central Hospital.Subjects and Methods: A cross-sectional descriptive study was conducted on 44 patients with closed tibial shaft fractures treated using SIGN intramedullary nails at 108 Military Central Hospital from January 2023 to May 2025.Results: Closed reduction was achieved in 88.64% of patients, while open reduction was required in 11.36%. A total of 43 out of 44 patients had both proximal and distal locking screws inserted. Three locking screws were used in 75.00% of cases, and four screws in 4.55%. A central screw was utilized in most cases (93.18%). Primary wound healing occurred in 90.91% of surgical incisions and 97.73% of locking sites. All patients had good SIGN nail positioning without joint involvement. Postoperative limb alignment was satisfactory (straight axis) in 84.09% of cases. According to the Larson–Böstman criteria, 84.09% of patients had excellent outcomes, with no cases of fair or poor results. Operative time and surgical technique factors did not significantly affect short-term treatment outcomes (p > 0.05).Conclusion: Most patients achieved primary wound healing and satisfactory limb alignment after intramedullary nailing. The majority of patients demonstrated good treatment outcomes
Keywords: Closed tibial shaft fracture, intramedullary nail, 108 Military Central Hospital